'When we were children we had dreams, then we came to Dhaka to survive': urban stories connecting loss of wellbeing, displacement and (im)mobility. (21st April 2021) - Ayeb-Karlsson, Sonja
ABSTRACT: This article uses storytelling methodology to investigate the connections between urban climate-induced loss of wellbeing and (im)mobility in Bhola Slum, an informal settlement in Dhaka, Bangladesh. The settlement houses Internally Displaced People from the southern coast who built and named the slum after their home - Bhola Island. The storytelling sessions revealed that loss of belonging, identity, quality of life and social value produced in people a desire to return. Nostalgic storylines of home also shaped the narratives of the children born in the slum who often referred to the island as their home. Some women felt that the move had resulted in more liberty, but also claimed that it had increased the risk of social punishment and stigmatisation. Social stigma often extended from parents to children. More women than men reported feeling unsafe, depressed and anxious. Mental and physical ill health were both common consequences of the compromised living and working conditions of the slum. Loss of health (due to injuries or disease) damaged people's wellbeing and pushed already fragile families into a downward spiral with no escape. Few empirical studies investigate 'trapped' populations and non-economic losses and damages in urban environments. The insights gained from this work can therefore help safeguard vulnerable populations worldwide and build more robust climate policy frameworks.